J /ψ Elliptic Flow in Pb-Pb Collisions at sNN =5.02 TeV - Acharya, S.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2017)
We report a precise measurement of the J/ψ elliptic flow in Pb-Pb collisions at sqrt[s_{NN}]=5.02 TeV with the ALICE detector at the LHC. The J/ψ mesons are reconstructed at midrapidity (|y|<y<p_{T}
Keywords: Physics; Algorithm; Computer science; https://purl.org/pe-repo/ocde/ford#1.02.01